Formation of insurance reserves and their feature conducting accounting, expenses and cost of insurance operations of activity of insurance companies (Journal of Economic Research & Business Administration, 2015)
In article formation of insurance reserves and feature conducting accounting of reserves, expenses and cost of insurance operations is considered. Insurance reserves - funds of insurance fund which the insurer forms of insurance premiums (insurance premium) which the insurer under the insurance contract pays. Insurance reserves are intended for ensuring execution with the insurer and/or the overcautious person of obligations for insurance and/or reinsurance. Expenses represent cost of insurance operations and include the following expenses of the insurer: compensation of regular and freelance employees of insurance company, tenancy, payment for the electric power, heating, water supply, post and cable, telephone expenses, travel expenses, other expenses of the company connected with performance by her to the activity. The structure and structure of expenses are defined by two interconnected economic processes: repayment of obligations to insurers and financing of activity of insurance company. In aggregate these expenses represent cost of insurance operations.
Keywords: insurance reserves; expenses of insurance companies; insurance operations; cost of insurance operations; insurance tariffs